Structural Evolution and Electronic Properties of Intermediate Sized Tin(n=33--60) Clusters. Issue 12 (25th October 2021) - Rodríguez‐Kessler, Peter L.; Rodríguez‐Domínguez, Adán R.; Muñoz‐Castro, Alvaro
Abstract: The structural evolution of Ti n ( n = 33 − 60 ) clusters has been investigated by using the systematic cluster growth method together with the many‐body Gupta potential. The lowest energy structures are further refined by using density functional theory computations within the accuracy of the Perdew‐Burke‐Ernzerhof (PBE) exchange‐correlation functional and a plane‐wave basis set. Using this approach, the structures and stability trends of Ti n clusters in the n = 13 − 32 size range previously reported, are reproduced. New clusters with enhanced stability are found for n = 33, 38, 41, 43, 46, 48, 50, 53, 55, and 58 sizes. Tightly packed structures dominate principally for these clusters in which the shape of the structures can be understood based on the encapsulated motif. The geometries of the clusters from Ti33 up to Ti60 adopt oblate forms which is in contrast to the smaller clusters. The vertical ionization potential (vIP) and vertical electron affinity (vEA) curves show a step behavior depending of the size range for n = 40 -- 60, while the chemical hardness decreases monotonically with the size, which is consistent with the d‐band center parameter. In contrast to previous reports, for n = 55 it is found that a distorted Mackay icosahedron is more stable than the regular one. The theoretical electronic properties for the most stable isomers of Ti n clusters are in good agreement with the available experimental data. Abstract : The structural evolution of Tin ( n = 33–60) clusters is investigated by using the systematic cluster growth method together with the many‐body Gupta potential, followed by a density functional theory reoptimization. New clusters with enhanced stability are found for n = 33, 38, 41, 43, 46, 48, 50, 53, 55, and 58 sizes.